Statistical optimization service traffic in heterogeneous information and communication networks - Ігнатов, В. О.; Гузій, М. М.; Ладигіна, О. А. (Problems of Informatization and Control, 2015)
Developed stochastic optimization model service traffic in heterogeneous information and communication networks